Private Predecision Information, Performance Measure Congruity, and the Value of Delegation* - BUSHMAN, ROBERT M.; INDJEJIKIAN, RAFFI J.; PENNO, MARK C. (Contemporary Accounting Research, 2000)
Abstract We use a linear contracting framework to study how the relation between performance measures used in an agent's incentive contract and the agent's private predecision information affects the value of delegating decision rights to the agent. The analysis relies on the idea that available performance measures are often imperfect representations of the economic consequences of managerial actions and decisions, and this, along with gaming possibilities provided to the agent by access to private predecision information, may overwhelm any benefits associated with delegation. Our analytical framework allows us to derive intuitive conditions under which delegation does and does not have value, and to provide new insights into the linkage between imperfections in performance measurement and agency costs.